Exploring students’ contentment level of the infrastructure at a public higher education institution in Malaysia / Wan Nurashikin Mahmood, Mohamad Ridhuan Mat Dangi and Khairul Anuar Mohd Ali - Mahmood, Wan Nurashikin; Mat Dangi, Mohamad Ridhuan; Mohd Ali, Khairul Anuar (Universiti Teknologi MARA Cawangan Pahang, 2014)
This paper attempts to assess the factors that influence the students’ satisfaction level towards higher learning education system. The study was conducted at a public university located in the east coast region of Malaysia involving 401 respondents. This study overviewed the students’ satisfaction towards the infrastructure provided by the university which includes the resource center or library service, ICT service, and the campus environment. This study used simple random sampling in selecting the respondents and descriptive statistics to analyse the data. The findings reveal that the services that gave the lowest satisfaction was the campus environment resulted from the lack of availability of parking space for students and lack of availability of food service in the campus and hostel. The university’s management should seriously consider these factors in order to improve the level of students’ satisfaction.